Back to the future: assessing the damage of 2004 Dhaka flood in the 2050 urban environment. (8th December 2015) - Khan, D.M.; Veerbeek, W.; Chen, A.S.; Hammond, M.J.; Islam, F.; Pervin, I.; Djordjević, S.; Butler, D.
Abstract: Planning to make a city flood resilient needs proper assessment of future conditions. Urban growth models are being used as a planning tool for city development. Within the project Collaborative Research in Flood Resilience in Urban Areas (CORFU), flood management strategies suitable for cities with varied geographic and socio‐economic conditions have been developed. In the paper, we adopted urban growth model to project the possible future conditions of Dhaka City, the rapidly developing capital of Bangladesh. Bangladesh lies in the delta of the Himalayan Mountain range and experiences frequent flooding. In 2004 an extreme nationwide flood event occurred, which caused major damage to Dhaka City. If the same event were to occur in 2050, it can be expected that the damage would increase significantly. Through the application of the urban growth, hydraulic and damage assessment models, we were able to determine the damage that can be expected to happen in 2050. The paper also describes the key factors that are important to determine this impact and the associated uncertainties.